Draft Twelfth Five Year Plan (2012-17) and Annual Plan 2012-13 Volume I Government of Assam - Planning Commission (Planning Commission, 2012)
Assam is the gateway to North East India with full of natural and man made growth. The extensive forest area of Assam is a house of different species and strains of natural flora and fauna as well as rich with valuable forest products, medicinal plants etc. The mighty Brahmaputra and its tributaries in the north and the Barak in the south made the two valleys fertile. The congenial agro-climatic condition assisted production of foodgrains, tea gardens and horticultural crops. Moreover, Assam is endowed with precious natural and mineral resources. The geographical area of the state is 78438 sq. km. which is 2.4 per cent of the country. Of the total area, 25.6 per cent is under forest, 322 thousand ha. is under Tea plantation and 3402 thousand ha is agricultural operational area.
Planning and Development Department Dispur, Assam